BID'AH DALAM PERSPEKTF FUQAHA DITINJAU DARI SEGI AL-SUNNAH - Faisal Muhammad Nur (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2017)
Any work that the Prophet (peace and blessings of Allah be upon him) and his companions have never done, should not be categorized into bid'ah dhalalah (heresy that is misleading) unless there is a clue that explains her misdeed and bid'ah divided into two parts: A). Bid'ah Hasanah (good bid'ah) is a heresy that corresponds to al-Sunnah before. B). Bid'ah Dhalalah (heresy that is misleading) is heresy that deviated with al-Sunnah before. Bid'ah hasanah covers various aspects of life both aspects of worship and aspects of mu'amalah.